Law and society - Vago, Steven; Barkan, Steven E., 1951- (New York: Routledge, 2021)
'This new edition of the landmark text Law and Society exposes readers to the dominant theoretical perspectives and sociological methods that are used to explain the interplay between law and society. This twelfth edition continues to preserve Professor Vago's voice, while Steven E. Barkan's use of chapter outlines and summaries, learning objectives, key terms, and additional readings maintains the text's accessibility for today's readers. The book's foundational approach is brought fully up-to-date with current events and new studies throughout that illustrate how legal forces shape and influence society, and vice versa. These additions include: Updated data on trial and conviction data in federal district courts Updated data on sexual harassment of attorneys and new data on representation of women and people of color among law school faculty New discussions of legal issues arising from the Covid-19 pandemic. The twelfth edition of Law and Society is a cornerstone companion for one-semester undergraduate courses in Law and Society, Sociology of Law, and Introduction to Law offered within departments of Sociology, Criminal Justice, and Political Science'--
Shaizimah Binti Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216393 / OC/ Bookline Services
Includes bibliographical references and index. (269-298 pages)
Keywords: Sociological jurisprudence